2017
DOI: 10.1111/1748-8583.12126
|View full text |Cite
|
Sign up to set email alerts
|

Organisational consequences of asymmetries in task dependence: the moderating role of HR practices

Abstract: This study integrates recent advances in interdependence theory with the literature on commitment-based HR practices. New research on interdependence theory suggests that differences, or asymmetries, in task dependence among organisational members can cause interests to diverge. Prior research has shown that this can negatively affect interpersonal relations, individual outcomes and team processes. However, these insights gained on the dyadic, individual and team levels of analysis have not yet been explored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…In accordance with prior research, we conceptualized company performance to comprise both organizational and operational aspects (Combs, Crook, & Shook, 2005;Venkatraman & Ramanujam, 1986). Thus, in addition to one item asking about the company's overall performance, we included one item for organizational performance (increase in market shared) and one for operational performance (business efficiency; for a similar approach, see, e.g., De Jong, Kunze, & Bruch, 2017). Items were average to obtain one performance score per company (α = 0.80).…”
Section: Company Performancementioning
confidence: 99%
“…In accordance with prior research, we conceptualized company performance to comprise both organizational and operational aspects (Combs, Crook, & Shook, 2005;Venkatraman & Ramanujam, 1986). Thus, in addition to one item asking about the company's overall performance, we included one item for organizational performance (increase in market shared) and one for operational performance (business efficiency; for a similar approach, see, e.g., De Jong, Kunze, & Bruch, 2017). Items were average to obtain one performance score per company (α = 0.80).…”
Section: Company Performancementioning
confidence: 99%
“…Trust is commonly defined as ‘a psychological state comprising the intention to accept vulnerability based upon positive expectations of the intentions or behaviour of another’ (Rousseau, Sitkin, Burt, & Camerer, 1998, p. 395; see also Bozic, Siebert, & Martin, 2019). Or as De Jong et al (2017, p. 78) put it ‘trust arises only when a vulnerability that could have been abused was not abused’. These ‘positive expectations’ are based on perceptions about the other party and its trustworthiness, resulting from past positive mutual interactions (Tzafrir & Dolan, 2004), whereas the ‘intention to accept vulnerability’ is a risk‐taking act.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, if employees could trust the organisation without having personalised knowledge of each decision maker and key actor, the organisation should be more efficient (Kramer, 1999). Impersonal trust is based on roles, systems and reputation, while interpersonal trust is based on interpersonal interaction between individuals within a particular relationship and as a whole those compose an intra‐organisational trust climate (De Jong et al, 2017; Holtgrave et al, 2020). Trust in the organisation is employee's evaluation and confidence that the organisation will perform an action that is beneficial or at least not detrimental to him or her (Donia & Tetrault Sirsly, 2016; Maguire & Phillips, 2008).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hence, viewed together, this line of research revealed that asymmetries exist and can have both negative as well as positive effects on work relationships, individuals, and teams. Building further upon this, we set-up an organizational-level study to find out if these effects might even shape organizational performance (De Jong, Kunze, & Bruch, 2017).…”
Section: Horizontal Asymmetriesmentioning
confidence: 99%